BINDING AGENT AND PREPARATION METHOD THEREOF AND LITHIUM ION BATTERY
The SBR adhesive prepared by soap-free emulsion polymerization method solves the problem of insufficient bonding strength of existing SBR adhesives, achieves high bonding strength and structural regularity, and improves the energy density and safety performance of lithium-ion batteries. .
Patent Information
- Application Number
- CN202411014267.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The lack of bonding power of existing SBR adhesives affects the electrochemical performance of lithium-ion batteries.
The soap-free emulsion polymerization method is adopted, and a mixture of water and cosolvent is used as the dispersion medium of the polymerization reaction system, butadiene, styrene, unsaturated polyolefins are used as the main monomers, and functional monomers, electrolytes and dispersion additives are combined. A medium- and high-temperature continuous dropping polymerization process was carried out to prepare an SBR adhesive with high bonding force and structural regularity.
The prepared SBR binder has high molecular weight, good structural regularity, high purity, high temperature resistance, excellent flame retardant and environmentally friendly properties. It can form a good wetting interface and bonding layer with the negative electrode active substance and conductive agent to improve adhesion. The junction force reduces the swelling and rolling rebound of the negative electrode material, thereby improving the energy density and safety performance of the battery.
Smart Images

Figure CN118930702B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a binder and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In recent years, with the rapid development of lithium-ion battery manufacturing technology, various large-capacity, high-energy energy storage devices have gradually been widely used in various common facilities and equipment in people's lives, making people's daily work and life better.
[0003] For example, with the development of new energy vehicles, various high-performance power lithium-ion batteries have been widely used in the power systems of new energy vehicles due to their large energy and fast energy release. However, although lithium-ion power batteries have many advantages, they still have some fatal defects, such as poor thermal stability, which can easily lead to battery breakdown, short circuit, combustion and explosion due to thermal runaway, which has a significant impact on the user's life safety and user experience. Therefore, the development of power batteries with good safety performance is of great significance to promoting the development of the new energy industry and the electric vehicle industry.
[0004] Among them, electrode binder is one of the essential materials of lithium-ion batteries. Although its content in the electrode is relatively small, it has an important influence on the electrochemical performance of lithium-ion batteries. The main function of electrode binder is to bind the active material, conductive agent and current collector together.
[0005] At present, the main binders used in lithium-ion batteries are styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose, polyacrylic acid, etc. Among them, SBR binder has good flexibility, but insufficient bonding strength. When used in lithium-ion batteries, it is not conducive to improving the electrochemical performance of lithium-ion batteries. Summary of the invention
[0006] In order to solve the problem of insufficient bonding strength of SBR binders in the prior art, the present invention provides a method for preparing a binder. The binder prepared by the preparation method can form a good wetting interface and bonding layer with the negative electrode active material and the conductive agent, and form a flexible cross-linked network bonding structure with the substrate, which helps to improve the bonding strength, thereby solving the problem of insufficient bonding strength of the binder in the prior art.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] A method for preparing a binder comprises the following steps:
[0009] S1: According to weight parts, 35-55 parts of water, 1-2 parts of functional monomers, 2-3 parts of styrene, 0.1-2 parts of electrolytes, 0.01-0.1 parts of chelating agents, and 0.08-0.1 parts of pH regulators are mixed to obtain a kettle bottom material;
[0010] S2: Mix 1 to 5 parts of a cosolvent and 0.3 to 1.1 parts of an initiator by weight to obtain an initiator phase;
[0011] S3: Mix 5 to 10 parts of butadiene, 5 to 13 parts of styrene, 3 to 5 parts of unsaturated polyolefin, and 0.1 to 1.2 parts of a molecular weight regulator by weight to obtain an oil phase;
[0012] S4: Mix 0.5 to 3 parts of a dispersing aid, 1 to 2.9 parts of an electrolyte, 2 to 4 parts of a functional monomer, and 2 to 4 parts of a cosolvent according to weight parts to obtain a functional monomer phase;
[0013] S5: Under stirring conditions, heating the kettle bottom material to 40° C. to 70° C., adding part of the initiator phase, and reacting at a constant temperature for 1-3 hours, adding the oil phase, the remaining initiator phase, and the functional monomer phase, heating to 70° C. to 90° C. and reacting for 2-3 hours to obtain a reaction solution;
[0014] S6: Add 0.05-0.5 parts of a degassing agent to the reaction solution by weight, perform vacuum degassing and cool the reaction solution until the temperature drops to 30°C-40°C, then add 0.05-0.1 parts of a terminator and 0.1-0.3 parts of a pH adjuster, adjust the pH value of the reaction product to 6-8, and obtain a binder.
[0015] Optionally, the co-solvent is selected from at least one of ethanol, ethylene glycol, N-methylpyrrolidone, ethyl ether, propanol, isopropanol, propylene glycol, butyl acetate, dimethyl carbonate, and vinyl alcohol.
[0016] Optionally, the unsaturated polyolefin is selected from at least one of isoprene, cyclopentadiene, dibutadiene, cyclohexadiene and octadiene.
[0017] Optionally, the functional monomer is selected from at least one of unsaturated carboxylic acids and their ester salts, unsaturated sulfonic acids and their ester salts, unsaturated organosiloxanes, vinyl pyridine or vinyl pyrrolidone.
[0018] Optionally, the electrolyte is an organic phosphate polymer.
[0019] Optionally, the organic phosphate polymer is selected from at least one of ammonium polyphosphate, lithium polyphosphate, sodium hexametaphosphate, ammonium tripolyphosphate, and ammonium hypophosphite.
[0020] Optionally, the dispersing aid is selected from at least one of unsaturated organic phosphate compounds or thiocyanate compounds.
[0021] Optionally, the pH adjuster is selected from at least one of sodium carbonate, potassium carbonate, lithium carbonate, sodium bicarbonate, and sodium thiosulfate.
[0022] Another object of the present invention is to provide an adhesive, which is prepared by the adhesive preparation method as described above.
[0023] Another object of the present invention is to provide a lithium ion battery comprising the binder as described above.
[0024] The beneficial effects of the present invention are:
[0025] The preparation method of the binder provided by the present invention adopts a soap-free emulsion polymerization method, uses a mixture of water and a cosolvent as a dispersion medium of a polymerization reaction system, uses butadiene, styrene, and unsaturated polyolefins as the main monomers of the polymerization reaction system, and cooperates with functional monomers and electrolyte dispersing aids, adopts a medium-high temperature polymerization process, and prepares an SBR binder with a large molecular weight, good structural regularity, high purity, good high and low temperature resistance and solvent resistance, and excellent flame retardancy and environmental protection performance. The appearance of the binder is a uniform milky white liquid, has a low content of small molecule residual volatile substances, excellent mechanical stability and chemical stability, fast film formation and drying speed, can form a good wetting interface and bonding layer with the negative electrode active material and the conductive agent, and form a flexible cross-linked network bonding structure with the substrate, improve the bonding force, effectively reduce the swelling and roller rebound of the negative electrode material, thereby improving the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0027] Figure 1 This is a particle size distribution diagram of the binder prepared in Example 1 of the present invention;
[0028] Figure 2 This is a particle size distribution diagram of the binder prepared in Example 2 of the present invention;
[0029] Figure 3 This is a particle size distribution diagram of the binder prepared in Example 3 of the present invention;
[0030] Figure 4 This is a particle size distribution diagram of the binder prepared in Example 4 of the present invention;
[0031] Figure 5 This is a particle size distribution diagram of the binder prepared in Example 5 of the present invention;
[0032] Figure 6This is a particle size distribution diagram of the binder prepared in Comparative Example 1 of the present invention;
[0033] Figure 7 This is a particle size distribution diagram of the binder prepared in Comparative Example 2 of the present invention;
[0034] Figure 8 This is a particle size distribution diagram of the binder prepared in Comparative Example 3 of the present invention;
[0035] Fig. 9 This is a particle size distribution diagram of the binder prepared in Comparative Example 4 of the present invention;
[0036] Fig.10 This is a particle size distribution diagram of the binder prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0038] In order to solve the problem of insufficient bonding force of SBR binders in the prior art, the present invention provides a method for preparing a binder, the preparation method comprising the following steps:
[0039] S1: According to weight parts, 35-55 parts of water, 1-2 parts of functional monomers, 2-3 parts of styrene, 0.1-2 parts of electrolytes, 0.01-0.1 parts of chelating agents, and 0.08-0.1 parts of pH regulators are mixed and stirred to obtain a kettle bottom material;
[0040] S2: Mix 1 to 2 parts of a cosolvent and 0.3 to 1.1 parts of an initiator by weight to obtain an initiator phase;
[0041] S3: Mix 5 to 10 parts of butadiene, 5 to 13 parts of styrene, 3 to 5 parts of unsaturated polyolefin, and 0.1 to 1.2 parts of molecular weight regulator according to weight parts, stir evenly, and obtain an oil phase;
[0042] S4: According to weight parts, 0.5 to 3 parts of a dispersing aid, 1 to 2.9 parts of an electrolyte, 2 to 4 parts of a functional monomer, and 2 to 4 parts of a cosolvent are mixed and stirred uniformly to obtain a functional monomer phase;
[0043] S5: Under stirring conditions, heat the kettle bottom material to 40°C to 70°C, add part of the initiator phase, preferably add 10%-20% of the mass of the initiator phase, and react at a constant temperature for 1-3 hours, then add the oil phase, the remaining initiator phase, and the functional monomer phase, preferably by dropping, and preferably dropwise at a uniform speed for 6-8 hours. After the dropwise addition is completed, heat to 70°C to 90°C and keep warm for 2-3 hours. Preferably, during the insulation process, sample and test the conversion rate every hour until the conversion rate reaches 95% to 99%, then stop the reaction to obtain a reaction solution;
[0044] S6: Add 0.05-0.5 parts of degassing agent to the reaction solution by weight, degas and cool under vacuum until the temperature drops to 30°C-40°C, then add 0.05-0.1 parts of terminator and 0.1-0.3 parts of pH adjuster, adjust the pH value of the reaction product to 6-8, stir at a constant speed for 0.5-1.5 hours, discharge, demagnetize, filter, and package to obtain a binder.
[0045] The preparation method of the binder provided by the present invention adopts a soap-free emulsion polymerization method, uses a mixture of water and a cosolvent as a dispersion medium of a polymerization reaction system, uses butadiene, styrene, and unsaturated polyolefins as the main monomers of the polymerization reaction system, and cooperates with functional monomers and electrolyte dispersing aids, adopts a medium-high temperature polymerization process, and prepares an SBR binder with a large molecular weight, good structural regularity, high purity, good high and low temperature resistance and solvent resistance, and excellent flame retardancy and environmental protection performance. The appearance of the binder is a uniform milky white liquid, has a low content of small molecule residual volatile substances, excellent mechanical stability and chemical stability, fast film formation and drying speed, can form a good wetting interface and bonding layer with the negative electrode active material and the conductive agent, and form a flexible cross-linked network bonding structure with the substrate, improve the bonding force, effectively reduce the swelling and roller rebound of the negative electrode material, thereby improving the energy density of the battery.
[0046] Specifically, the preferred co-solvent of the present invention is selected from at least one of ethanol, ethylene glycol, N-methyl pyrrolidone, ether, propanol, isopropanol, propylene glycol, butyl acetate, dimethyl carbonate, and vinyl alcohol; the preferred unsaturated polyolefin is selected from at least one of isoprene, cyclopentadiene, dimer butadiene, cyclohexadiene, and octadiene; the role of introducing unsaturated polyolefins in the present invention is to increase the cross-linking points inside the molecule, adjust the regularity between molecules, increase the cross-linking density of the adhesive, enhance the flexibility of the adhesive, and reduce roller pressure rebound and swelling.
[0047] The present invention preferably selects at least one of the functional monomers from unsaturated carboxylic acids and their ester salts, unsaturated sulfonic acids and their ester salts, unsaturated organosiloxanes, vinyl pyridine or vinyl pyrrolidone, so as to improve the wetting performance of the binder on the electrode active material and the current collector surface by introducing surface-active functional monomers, reduce interfacial energy, and improve bonding strength; and, by introducing vinyl pyridine and vinyl pyrrolidone, nitrogen heterocycles can be utilized to improve the conductivity of the binder molecular structure and reduce internal resistance.
[0048] Specifically, the preferred functional monomer of the present invention is at least one selected from sodium acrylate, sodium methacrylate, allyl sulfonic acid sodium salt, 2-acrylamide-2-methylpropane sulfonic acid, maleic acid sodium salt, hexenoic acid sodium salt, butenedioic acid sodium salt, vinyl ether siloxane, and vinyl ester siloxane.
[0049] The electrolyte of the present invention is preferably an organic phosphate polymer, so that the organic phosphate polymer can be used to improve the stability of the binder during the synthesis process and improve the dispersion stability of the binder during the application and dispersion process.
[0050] Specifically, in the present invention, the preferred organic phosphate polymer is at least one selected from ammonium polyphosphate, lithium polyphosphate, sodium hexametaphosphate, ammonium tripolyphosphate, and ammonium hypophosphite.
[0051] The preferred chelating agent of the present invention is selected from one or more of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, citric acid, and diethylenetriaminepentaacetic acid, and is used for complexing impurities in water to improve water quality and product quality.
[0052] The preferred dispersing aid of the present invention is selected from at least one of unsaturated organic phosphate compounds or thiocyanate compounds, so that the bonding strength of the adhesive can be improved through the dispersing aid, and the flexibility, high temperature resistance and flame retardancy of the polymer molecular chain can be improved; and the dispersing aid is further preferably selected from at least one of methacrylate phosphate, acrylic acid monophosphate, acrylic acid diphosphate, and vinyl sulfate.
[0053] The preferred initiator of the present invention is a redox initiation system of a composite of an organic peroxide and an organic reducing substance. This type of organic initiator system can form a special reactive center point with an organic functional monomer and a macromolecular chain, and react different materials into the molecular structure in an orderly manner; specifically, the preferred initiator of the present invention is azobisisoheptanonitrile.
[0054] The preferred pH regulator of the present invention is selected from at least one of sodium carbonate, potassium carbonate, lithium carbonate, sodium bicarbonate and sodium thiosulfate; the preferred molecular weight regulator is selected from one or more of dodecyl mercaptan, tetradecyl mercaptan and hexadecyl mercaptan; the preferred chelating agent is at least one of disodium ethylenediaminetetraacetate and tetrasodium ethylenediaminetetraacetate; the preferred degassing agent is selected from one or more of petroleum ether, white oil, polydimethylsiloxane and polyethylene glycol; the preferred terminator is selected from one or more of sodium dimethyldithiocarbamate, sodium nitrite and diethylhydroxylamine.
[0055] The invention adopts a soap-free emulsion polymerization method, uses a mixture of water and a cosolvent as a dispersion medium of a polymerization reaction system, uses butadiene, styrene and unsaturated polyolefins as main monomers of the polymerization reaction system, uses unsaturated carboxylic acids and their ester salts, unsaturated sulfonic acids and their ester salts, unsaturated organic siloxanes, vinyl pyridine or vinyl pyrrolidone as functional monomers, uses organic polymer phosphates as electrolytes of the polymerization reaction system, uses unsaturated organic phosphates or thiocyanates as dispersion aids of the polymerization reaction system, uses a redox initiation system of a composite of an organic peroxide and an organic reducing substance as an initiator of the polymerization reaction system, and adopts a polymerization process of continuous dripping at medium and high temperatures to prepare a lithium ion power battery negative electrode SBR binder with large molecular weight, good structural regularity, high purity, good high and low temperature resistance and solvent resistance, and excellent flame retardancy and environmental protection performance.
[0056] The appearance of the binder is a uniform milky white liquid, with low content of small molecule residual volatile substances, excellent mechanical stability and chemical stability, fast film-forming and drying speed, and can form a good wetting interface and bonding layer with the negative electrode active material and the conductive agent, and form a flexible cross-linked network bonding structure with the substrate, effectively reducing the swelling and roller rebound of the negative electrode material, thereby improving the energy density of the battery. At the same time, the binder has a large number of regular flame-retardant segment structures, which can form a good coating and dispersion structure with the electrode active material. After contacting with the electrolyte, it can stretch and penetrate into the electrolyte, and form a stable electron and ion channel between the electrolyte and the electrode active material, thereby improving the stability and flame retardancy of the battery, reducing the cycle charge and discharge internal resistance, and giving the lithium-ion battery good cycle charge and discharge performance, so that the lithium-ion power battery has good safety performance and cycle life. This SBR binder can be used as a negative electrode binder for solid, semi-solid, liquid and liquid flow lithium-ion power batteries.
[0057] The SBR latex prepared by the preparation method provided by the present invention has the characteristics of uniform particle size distribution, suitable particle size, good fluidity, good comprehensive stability, etc. When the SBR binder emulsion is used to prepare a lithium-ion power battery, a good infiltration, coating, and dispersion structure are formed between the binder and the conductive agent, the electrode active material, and the current collector foil, and an excellent mesh bonding structure is formed. At the same time, a good electron and ion channel is formed between the electrode active material, the electrolyte, and the current collector, reducing the internal cycle resistance of the battery, improving the cycle charge and discharge performance, flame retardant performance, and service life, thereby reducing the charge and discharge heat release of the battery and reducing the flammability of the lithium-ion power battery. Compared with lithium-ion power batteries prepared by other binders, lithium-ion power batteries prepared by the SBR binder latex prepared by the present invention have lower internal resistance, higher flame retardancy, better cycle charge and discharge performance, and longer service life, which fundamentally improves the safety performance of lithium-ion power batteries.
[0058] Another object of the present invention is to provide an adhesive, which is prepared by the adhesive preparation method as described above.
[0059] The binder provided by the present invention adopts a synthetic process of soap-free emulsion polymerization, uses a special functional monomer as a reactive surfactant of a polymerization reaction system, uses organic phosphates as electrolytes, uses unsaturated phosphates as dispersants, and adopts a polymerization process of continuous dripping at medium and high temperatures, thereby improving the purity, high and low temperature resistance, thermal stability, and bonding strength of the SBR binder from a structural perspective, fundamentally improving the flame retardancy and cycle performance of lithium-ion power batteries, and reducing the internal resistance of the batteries, thereby enabling lithium-ion power batteries to have intrinsic safety performance, reducing the use risks of users, and having important significance for promoting the safe development of lithium-ion power batteries.
[0060] The binder provided by the present invention is used for bonding and shaping the conductive agent and active material in the lithium ion negative electrode conductive coating slurry, imparting good bonding strength between the electrocoating and the metal current collector foil, enhancing the stability and low internal resistance performance of the internal structure of the lithium ion battery, improving the cycle performance and safety and flame retardant performance of the lithium ion power battery, and can be used as a negative electrode binder for solid, semi-solid and liquid lithium ion power batteries, and belongs to the field of emulsion polymerization in polymer material synthesis technology.
[0061] Another object of the present invention is to provide a lithium ion battery, which includes the binder as described above.
[0062] The lithium ion battery provided by the present invention adopts a synthetic process of a binder using soap-free emulsion polymerization, uses a special functional monomer as a reactive surfactant of a polymerization reaction system, uses an organic phosphate as an electrolyte, uses an unsaturated phosphate ester as a dispersant, and uses a polymerization process of continuous dripping at medium and high temperatures, thereby improving the purity, high and low temperature resistance, thermal stability, and bonding strength of the SBR binder from a structural perspective, fundamentally improving the flame retardancy and cycle performance of the lithium ion power battery, and reducing the internal resistance of the battery, thereby enabling the lithium ion power battery to have an intrinsically safe performance, reducing the use risk of users, and having important significance for promoting the safe development of lithium ion power batteries.
[0063] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0064] Example 1
[0065] This embodiment provides a method for preparing a binder, and the preparation method comprises the following steps:
[0066] S1: According to the weight ratio, 45 parts of pure water, 1.9 parts of functional monomer sodium allyl sulfonate, 2.6 parts of styrene, 1.9 parts of electrolyte lithium polyphosphate, 0.08 parts of chelating agent disodium ethylenediaminetetraacetate, and 0.09 parts of pH adjuster sodium carbonate are added to a bottom material batching tank and continuously stirred and dispersed to obtain bottom material;
[0067] S2: According to the weight ratio, 2.8 parts of the co-solvent ethylene glycol and 0.8 parts of the initiator azobisisoheptanenitrile were added into the initiator batching tank, and the mixture was stirred and mixed to obtain an initiator phase;
[0068] S3: Add 9.5 parts of butadiene, 12.5 parts of styrene, 3.1 parts of unsaturated polyolefin isoprene, and 0.5 parts of molecular weight regulator dodecyl mercaptan into an oil phase monomer preparation tank according to weight parts, stir and mix evenly to obtain an oil phase;
[0069] S4: according to the weight parts, 2.6 parts of dispersing aid methacrylate phosphate, 1.6 parts of electrolyte lithium polyphosphate, 3 parts of functional monomer sodium allyl sulfonate, and 3 parts of co-solvent ethylene glycol are added into the functional monomer preparation tank, and stirred and mixed evenly to obtain the functional monomer phase;
[0070] S5: Add the bottom material in the bottom material preparation tank into a clean 300L polymerization reactor at once, stir and heat to 60°C, add 0.4 parts of the initiator phase, start timing the bottoming reaction, react for 3 hours, start dripping the oil phase, the remaining initiator phase, and the functional monomer phase at the same time, and drip at a constant speed for 6 hours; after the dripping is completed, heat to 75°C and keep warm for 3 hours. During the insulation process, take samples every hour to test the conversion rate. After the conversion rate reaches 97%, stop the reaction to obtain a reaction solution;
[0071] S6: Add 0.04 parts of petroleum ether as a degassing agent to the reactor, start vacuum degassing and cooling, when the temperature drops to 35°C, add 0.04 parts of sodium dimethyldithiocarbamate as a terminator, add 0.3 parts of sodium carbonate as a pH adjuster, adjust the pH value of the reaction product to 7, and stir at a constant speed for 1.5 hours. After discharging, demagnetization, multi-stage filtration, and packaging, a binder emulsion is obtained, with a solid content of 40.32%, a viscosity of 26.69 cps, and a particle size of 161.87 nm (see the particle size distribution diagram). Figure 1 The pH value is 7.1, and the test results of physical properties are shown in Appendix 1.
[0072] Example 2
[0073] This embodiment provides a method for preparing a binder, which differs from the preparation method of embodiment 1 in that:
[0074] S5: Add the bottom material in the bottom material preparation tank into a clean 300L polymerization reactor at once, stir and heat to 70°C, add 0.6 parts of the initiator phase, start timing the bottoming reaction, react for 3 hours, start dripping the oil phase, the remaining initiator phase, and the functional monomer phase at the same time, and drip at a constant speed for 7 hours; after the dripping is completed, heat to 85°C and keep warm for 2 hours. During the insulation process, take samples every hour to test the conversion rate. After the conversion rate reaches 98%, stop the reaction to obtain a reaction solution;
[0075] S6: Add 0.3 parts of degassing agent white oil to the reactor, start vacuum degassing and cooling, when the temperature drops to 35°C, add 0.04 parts of terminator sodium nitrite, add 0.3 parts of pH adjuster sodium carbonate, adjust the pH value of the reaction product to 7, and stir at a constant speed for 1.5 hours. After discharging, demagnetization, multi-stage filtration, and packaging, a binder emulsion is obtained, with a solid content of 40.50%, a viscosity of 25.02 cps, and a particle size of 156.73 nm (see the particle size distribution diagram). Figure 2 The pH value is 7.02, and the test results of physical properties are shown in Appendix 1.
[0076] Example 3
[0077] This embodiment provides a method for preparing a binder, which differs from the preparation method of embodiment 1 in that:
[0078] S5: Add the bottom material in the bottom material preparation tank into a clean 300L polymerization reactor at once, stir and heat to 70°C, add 0.7 parts of the initiator phase, start timing the bottoming reaction, react for 3 hours, start dripping the oil phase, the remaining initiator phase, and the functional monomer phase at the same time, and drip at a uniform speed for 8 hours; after the dripping is completed, heat to 80°C and keep warm for 2 hours. During the insulation process, take samples every hour to test the conversion rate. When the conversion rate reaches 98%, stop the reaction to obtain a reaction solution;
[0079] S6: Add 0.5 parts of petroleum ether as a degassing agent to the reactor, start vacuum degassing and cooling, when the temperature drops to 35°C, add 0.04 parts of sodium dimethyldithiocarbamate as a terminator, add 0.3 parts of sodium carbonate as a pH adjuster, adjust the pH value of the reaction product to 7, and stir at a constant speed for 1.5 hours. After discharging, demagnetization, multi-stage filtration, and packaging, a binder emulsion is obtained, with a solid content of 40.46%, a viscosity of 26.12 cps, and a particle size of 152.99 nm (see the particle size distribution diagram for details). Figure 3 The pH value is 7.06, and the test results of physical properties are shown in Appendix 1.
[0080] Example 4
[0081] This embodiment provides a method for preparing a binder, and the preparation method comprises the following steps:
[0082] S1: According to the weight ratio, 35 parts of pure water, 1 part of the functional monomer sodium allyl sulfonate, 2.1 parts of styrene, 0.1 parts of electrolyte lithium polyphosphate, 0.01 parts of chelating agent disodium ethylenediaminetetraacetate, and 0.08 parts of pH adjuster sodium carbonate are added to a bottom material batching tank and continuously stirred and dispersed to obtain bottom material;
[0083] S2: According to the weight ratio, 1 part of the co-solvent ethylene glycol and 0.3 parts of the initiator azobisisoheptanenitrile were added into the initiator batching tank, and stirred and mixed to obtain the initiator phase;
[0084] S3: Add 5 parts of butadiene, 5 parts of styrene, 5 parts of unsaturated polyolefin isoprene, and 0.1 parts of molecular weight regulator dodecyl mercaptan into an oil phase monomer batching tank according to weight parts, stir and mix evenly to obtain an oil phase;
[0085] S4: Add 3 parts of dispersing aid methacrylate phosphate, 2.9 parts of electrolyte lithium polyphosphate, 2 parts of functional monomer sodium allyl sulfonate, and 2 parts of co-solvent ethylene glycol into a functional monomer preparation tank according to weight parts, stir and mix evenly to obtain a functional monomer phase;
[0086] S5: Add the bottom material in the bottom material preparation tank into a clean 300L polymerization reactor at once, stir and heat to 70°C, add 0.2 parts of the initiator phase, start timing the bottoming reaction, react for 3 hours, start dripping the oil phase, the remaining initiator phase, and the functional monomer phase at the same time, and drip at a uniform speed for 8 hours; after the dripping is completed, heat to 75°C and keep warm for 3 hours. During the insulation process, take samples every hour to test the conversion rate. After the conversion rate reaches 97%, stop the reaction to obtain a reaction solution;
[0087] S6: Add 0.04 parts of petroleum ether as a degassing agent to the reactor, start vacuum degassing and cooling, when the temperature drops to 35°C, add 0.04 parts of sodium dimethyldithiocarbamate as a terminator, add 0.3 parts of sodium carbonate as a pH adjuster, adjust the pH value of the reaction product to 7, and stir at a constant speed for 1.5 hours. After discharging, demagnetization, multi-stage filtration, and packaging, a binder emulsion is obtained, with a solid content of 40.32%, a viscosity of 26.69 cps, and a particle size of 161.87 nm (see the particle size distribution diagram). Figure 4 The pH value is 7.1, and the test results of physical properties are shown in Appendix 1.
[0088] Example 5
[0089] This embodiment provides a method for preparing a binder, and the preparation method comprises the following steps:
[0090] S1: According to the weight ratio, 55 parts of pure water, 2 parts of functional monomer sodium allyl sulfonate, 3 parts of styrene, 1 part of electrolyte lithium polyphosphate, 0.5 parts of chelating agent disodium ethylenediaminetetraacetate, and 0.09 parts of pH adjuster sodium carbonate are added into a bottom material batching tank and continuously stirred and dispersed to obtain bottom material;
[0091] S2: Add 5 parts of co-solvent ethylene glycol and 1.1 parts of initiator azobisisoheptanenitrile into an initiator batching tank according to weight parts, stir and mix evenly to obtain an initiator phase;
[0092] S3: Add 7 parts of butadiene, 9 parts of styrene, 4 parts of unsaturated polyolefin isoprene, and 1.2 parts of molecular weight regulator dodecyl mercaptan into an oil phase monomer batching tank according to weight parts, stir and mix evenly to obtain an oil phase;
[0093] S4: Add 3 parts of dispersing aid methacrylate phosphate, 2.9 parts of electrolyte lithium polyphosphate, 4 parts of functional monomer sodium allyl sulfonate, and 4 parts of co-solvent ethylene glycol into a functional monomer preparation tank according to weight parts, stir and mix evenly to obtain a functional monomer phase;
[0094] S5: Add the bottom material in the bottom material preparation tank into a clean 300L polymerization reactor at once, stir and heat to 65°C, add 0.7 parts of the initiator phase, start timing the bottoming reaction, react for 3 hours, start dripping the oil phase, the remaining initiator phase, and the functional monomer phase at the same time, and drip at a constant speed for 8 hours; after the dripping is completed, heat to 75°C and keep warm for 3 hours. During the insulation process, take samples every hour to test the conversion rate. After the conversion rate reaches 97%, stop the reaction to obtain a reaction solution;
[0095] S6: Add 0.04 parts of petroleum ether as a degassing agent to the reactor, start vacuum degassing and cooling, when the temperature drops to 35°C, add 0.04 parts of sodium dimethyldithiocarbamate as a terminator, add 0.3 parts of sodium carbonate as a pH adjuster, adjust the pH value of the reaction product to 7, and stir at a constant speed for 1.5 hours. After discharging, demagnetization, multi-stage filtration, and packaging, a binder emulsion is obtained, with a solid content of 40.32%, a viscosity of 26.69 cps, and a particle size of 161.87 nm (see the particle size distribution diagram for details). Figure 5 The pH value is 7.1, and the test results of physical properties are shown in Appendix 1.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 1 is that no unsaturated polyolefin is added; the particle size distribution of the prepared binder emulsion is shown in Figure 6 The test results of physical properties are shown in Appendix 1.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 1 is that no functional monomer is added; the particle size distribution diagram of the prepared binder emulsion is shown in Figure 7 The test results of physical properties are shown in Appendix 1.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 1 is that sodium dodecyl sulfate is used to replace the functional monomer sodium allyl sulfonate; the particle size distribution diagram of the prepared binder emulsion is shown in Figure 8 The test results of physical properties are shown in Appendix 1.
[0102] Comparative Example 4
[0103] The difference between this comparative example and Example 1 is that no electrolyte is added; the particle size distribution of the prepared binder emulsion is shown in Fig. 9 The test results of physical properties are shown in Appendix 1.
[0104] Comparative Example 5
[0105] The difference between this comparative example and Example 1 is that sodium chloride is used to replace the electrolyte lithium polyphosphate; the particle size distribution diagram of the prepared binder emulsion is shown in Fig.10The test results of physical properties are shown in Appendix 1.
[0106] The performance of the adhesives prepared in the above embodiments and comparative examples was tested, and the testing method was as follows:
[0107] Sampling: Sampling shall be carried out in accordance with SH / T1149;
[0108] Total solid content: The total solid content is tested in accordance with GB / T8298-2017;
[0109] Viscosity: Test the viscosity according to SH / T1152-2014;
[0110] pH value: Test the pH value in accordance with GB / T18012-2021;
[0111] Surface tension: Surface tension is tested according to SH / T1156-2014;
[0112] Mechanical stability: Mechanical stability is tested in accordance with SH / T1151.1-2019;
[0113] Chemical stability: Test the chemical stability according to SH / T1608-2014;
[0114] Particle size: The particle size was tested by NKT-N9 nano laser particle size analyzer.
[0115] The test results are shown in Table 1:
[0116] Table 1
[0117]
[0118] The binders prepared in the above embodiments and comparative examples were used to prepare negative electrodes for lithium-ion batteries, respectively. The formulas were as shown in Table 2 according to mass percentage:
[0119] Table 2
[0120]
[0121]
[0122] A lithium-ion battery is formed by using a negative electrode and a positive electrode prepared with the binder provided in each embodiment and comparative example, and an electrolyte, wherein the positive electrode is composed of 96.8wt% of lithium iron phosphate, 1.2wt% of a conductive agent, and 2.0wt% of a polyvinylidene fluoride resin; and the electrolyte is a lithium hexafluorophosphate electrolyte with a concentration of 1 mol / L.
[0123] The prepared lithium-ion batteries were subjected to performance tests, and the test methods were as follows:
[0124] Peel force test: Tested in accordance with GB / T 2792-2014;
[0125] Roller rebound, tensile strength and cyclic stretching times are tested in accordance with GB / T 42279-2022;
[0126] Dissolution test: Test according to SH / T 1050-2014.
[0127] The test results are shown in Table 3:
[0128] Table 3
[0129]
[0130] As can be seen from the above table, the adhesive provided by the present invention has good peeling force, improved bonding strength, less dissolution, less rebound, improved cross-linking structure, and increased number of cyclic stretching times, which helps to enhance the stability of the internal structure and low internal resistance performance of lithium-ion batteries, improve the cycle performance and safety and flame retardant properties of lithium-ion power batteries, and extend the service life.
[0131] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a binder, characterized in that: The steps include: S1: According to weight parts, 35-55 parts of water, 1-2 parts of functional monomers, 2-3 parts of styrene, 0.1-2 parts of electrolytes, 0.01-0.1 parts of chelating agents, and 0.08-0.1 parts of pH regulators are mixed to obtain a bottom material; S2: Mix 1-5 parts of a cosolvent and 0.3-1.1 parts of an initiator by weight to obtain an initiator phase; S3: Mix 5 to 10 parts of butadiene, 5 to 13 parts of styrene, 3 to 5 parts of unsaturated polyolefin, and 0.1 to 1.2 parts of a molecular weight regulator by weight to obtain an oil phase; S4: According to parts by weight, 0.5-3 parts of a dispersing aid, 1-2.9 parts of an electrolyte, 2-4 parts of a functional monomer, and 2-4 parts of a cosolvent are mixed to obtain a functional monomer phase; S5: Under stirring conditions, heating the kettle bottom material to 40°C-70°C, adding part of the initiator phase, reacting at a constant temperature for 1-3 hours, adding the oil phase, the remaining initiator phase, and the functional monomer phase, heating to 70°C-90°C and reacting at a constant temperature for 2-3 hours to obtain a reaction solution; S6: adding 0.04-0.5 parts of a degassing agent to the reaction solution by weight, degassing and cooling the reaction solution under vacuum until the temperature drops to 30° C.-40° C., adding 0.04-0.1 parts of a terminator and 0.1-0.3 parts of a pH adjuster, and adjusting the pH value of the reaction product to 6-8 to obtain a binder; The unsaturated polyolefin is selected from at least one of isoprene, cyclopentadiene, dibutylene, cyclohexadiene and octadiene; The functional monomer is selected from at least one of unsaturated carboxylic acids and their ester salts, unsaturated sulfonic acids and their ester salts, unsaturated organosiloxanes, vinyl pyridine or vinyl pyrrolidone; The electrolyte is an organic phosphate polymer.
2. The method for preparing the adhesive according to claim 1, characterized in that: The co-solvent is selected from at least one of ethanol, ethylene glycol, N-methylpyrrolidone, ethyl ether, propanol, isopropanol, propylene glycol, butyl acetate, dimethyl carbonate, and vinyl alcohol.
3. The method for preparing the adhesive according to claim 1, characterized in that: The organic phosphate polymer is selected from at least one of ammonium polyphosphate, lithium polyphosphate, sodium hexametaphosphate, ammonium tripolyphosphate and ammonium hypophosphite.
4. The method for preparing the adhesive according to claim 1, characterized in that: The dispersing aid is selected from at least one of unsaturated organic phosphate compounds and thiocyanate compounds.
5. The method for preparing the adhesive according to claim 1, characterized in that: The pH regulator is selected from at least one of sodium carbonate, potassium carbonate, lithium carbonate, sodium bicarbonate and sodium thiosulfate.
6. A binder, characterized in that: The adhesive is prepared by the method for preparing the adhesive according to any one of claims 1 to 5.
7. A lithium ion battery, characterized in that: Comprising the adhesive as claimed in claim 6.
Citation Information
Patent Citations
Lithium ion battery negative electrode aqueous binder
CN110982008A
Preparation method of adhesive for lithium ion battery
CN112321761A